PENGARUH KUALITAS PELAYANAN, PROMOSI PEMASARAN DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN RUMAH DI PERUMAHAN BUKIT BARELANG PIAYU - girsang, helpy; S.E.,M.M., Tiurniari Purba (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to determine the effect of Service Quality, Marketing Promotion and Customer Satisfaction on Purchasing Decisions at Bukit Barelang Piayu Housing. This study uses quantitative research methods analyzed with multiple linear regression analysis with the SPSS version 25 program. The population used is 133 people who have bought a house in Bukit Barelang Piayu Housing. While the sample used was 100 people using the Slovin formula. The results show that the partial effect of service quality on the purchase decision of Bukit Barelang Piayu houses has a significant effect. The effect of marketing promotion partially on the decision to buy the Bukit Barelang Piayu house has a significant effect. Partial effect of consumer satisfaction on the decision to buy a house Bukit Barelang Piayu has no significant effect. And there is a significant effect of service quality, marketing promotion and customer satisfaction simultaneously on the purchase decision of Bukit Barelang Piayu Housing.